KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA: STUDI KASUS KAWASAN UNIT PENGELOLAAN PT. AGROWIYANA, KABUPATEN TANJUNG JABUNG BARAT, JAMBI - Harnios Arief (Media Konservasi, 2011)
Development of forests into oil palm plantations have much impact, both directly and indirectly, on the environment within and surrounding the plantation.  Wildlife is one of the environmental component affected by oil palm plantation development.  The remaining forested areas inside the plantation area had the potential for wildlife encounter.  Based on field observations during the course of the study, 64 species were found in the area, which comprised of 43 species of birds, 7 species of mammals and 8 species of reptiles and amphibians.  Further analyses showed that the area had 7 species of mammals, 12 species of birds and 4 species of reptiles and amphibians which included in the category of rare/protected species.   Poaching, habitat destruction, indefinite land status, and the decline of feed quality were serious threat to the existence of wildlife in the area. Keywords: ecosystems, habitats, wildlife, and wildlife species diversity